Carbon disclosure and SDGs performance: adoption of green innovation in Indonesia - Tabah Rizki; Andrianto Widjaja; Dewi Shanty (Universitas Negeri Malang, 2023)
AbstractThis research aims to investigate the effect of Carbon Disclosure (CD) on SDGs Performance and explore the moderating role of Green innovation. The research data was taken from 220 public Mining and Energy companies in Indonesia during the 2017-2021 period. Data processing was carried out using the pooled least squares (PLS) model approach. The results of the study show that Carbon Disclosure (CD) and Green Innovation (GI) can significantly improve SDGs performance. The result of Green Innovation has been shown to significantly strengthen the positive effect of Carbon Disclosure (CD) on SDGs Performance.The implications of this research contribute to the literature related to signaling theory and RBV that the role of CD practices and GI play an important role in sustainability performance (SDGs). Then, companies must actively participate and continue to develop environmental care practices, incorporating issues into the formulation of company strategy through improving environmental performance such as implementing CD practices.Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh Carbon Disclosure (CD) terhadap Kinerja SDGs dan mengeksplorasi peran moderasi dari green innovation. Data penelitian diambil dari 220 perusahaan publik Energi dan Pertambangan di Indonesia selama periode 2017-2021. Data penelitian ini diolah dengan menggunakan pendekatan model Pooled Least Square (PLS). Hasil penelitian menunjukkan bahwa Carbon Disclosure (CD) dan Green Innovation (GI) dapat meningkatkan kinerja SDGs secara signifikan. Kehadiran Green Innovation terbukti secara signifikan memperkuat pengaruh positif Carbon Disclosure (CD) terhadap Kinerja SDGs. Implikasi penelitian ini berkontribusi pada literatur terkait signaling theory dan RBV bahwa peran praktik CD dan GI memegang peranan penting dalam meningkatkan kinerja keberlanjutan (SDGs). Kemudian, perusahaan harus berpartisipasi aktif dan terus mengembangkan praktik peduli lingkungan, memasukkan isu-isu ke dalam perumusan strategi perusahaan melalui peningkatan kinerja lingkungan seperti penerapan praktik CD.